FOOT CARE ADHERENCE AND ITS ASSOCIATION WITH DIABETIC FOOT ULCER SEVERITY AMONG PATIENTS WITH DIABETES MELLITUS - Marthalena Simamora; Henny Syapitri; Janno Sinaga; Listi Hasugian (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: Diabetic foot ulcers are a major complication of diabetes mellitus that increase the risk of infection, amputation, and poor quality of life. Adherence to foot care plays an important role in preventing ulcer progression, yet many patients have poor adherence. Objective: This study aimed to examine the association between foot care adherence and diabetic foot ulcer severity among patients with diabetes mellitus at the Asri Wound Care Center Clinic, Medan, Indonesia. Methods:This analytical cross-sectional study included 52 patients with diabetic foot ulcers selected through purposive sampling from a population of 109 patients. Foot care adherence was assessed using the Nottingham Assessment of Functional Footcare (NAFF) questionnaire, while ulcer severity was evaluated using the Wagner Classification. Data were analyzed using descriptive statistics and Spearman rank correlation. Results: More than half of the participants (53.8%) had poor foot care adherence, and Wagner Grade 1 was the most common ulcer severity (36.5%). Spearman rank correlation analysis showed a very strong negative correlation between foot care adherence and ulcer severity (r = −0.870, p < 0.001), indicating that better adherence was associated with lower ulcer severity. Conclusion: Foot care adherence was significantly associated with diabetic foot ulcer severity. Strengthening structured and continuous foot care education may improve adherence and reduce ulcer severity among patients with diabetes mellitus.